THE ROLE OF THE TECHNICAL STAFF IN THE FLIGHT SAFETY - M. V. Artyuhovich; O. G. Feoktistova (Научный вестник МГТУ ГА, 2016)
The article deals with the role of the maintenance personnel in the safety of flights. Statistical data and the reasons of wrong actions of the maintenance personnel are presented. The reasons of wrong actions of the personnel are analysed within the interrelation of personal and human factors.